Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Karyawan: Studi Kasus BPS Puncak Jaya - Timoti, Sealtiel; Suryaningtyas, Dianawati; Surjati, Endang (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
Each leader has a different perspective in leading an organization which is reflected in their respective leadership styles. The leadership style used must of course pay attention to the environment of the organization being led. This leadership style will ultimately affect the performance of the employees they lead. The objectives of this study are: 1) To analyze the influence of leadership style and work environment on the performance of employees at the BPS office in Puncak Jaya Regency, and 2) To analyze the influence of leadership style on the performance of employees at the BPS office in Puncak Jaya Regency. The study was conducted using a quantitative research approach and data was collected from observations and interviews. The analysis used in this study is quantitative data analysis. The analysis tools used are multiple linear regression, F test and t test. Leadership style and work environment have a positive and significant influence on employee performance. The percentage of influence is quite high. This means that employee performance can be influenced by two variables together, namely leadership style and work environment. Leadership style applied in a good work environment will increase employee performance. The leadership style possessed by a leader can affect employee performance. The better the leadership style possessed by a leader, the better the employee performance will be. In addition, the work environment partially has a significant effect on employee performance. This means that the work environment can affect employee performance. In an effort to improve employee performance, the government must have a good work environment.